Law As…Forest: Eco-logic, Stories and Spirits in Indigenous Jurisprudence - Kirsten Anker (Law Text Culture, 2017)
Taking up the suggestion that minor jurisprudence may consist either in the perpetual critique of the outsider to major jurisprudence or in the initiation of new grounds for jurisprudence, this essay wonders whether some forms of Indigenous jurisprudence – with a focus on the articulations of North American scholars – might do both. Emerging out of embodied relations with sentient forests, mountains, rivers and other non-humans, practices of Indigenous jurisprudence are at once a living critique of the disenchanted character of modern law, as well as a literal grounding of jurisprudence in relationships to place. The essay takes Indigenous jurisprudence on its own terms, particularly through ecologies as teacher, place-based stories and a participatory consciousness that experiences the spirit of the land, while attempting to articulate this jurisprudence in the idiom of the author’s own intellectual tradition, such as through the scientific foundations of Earth jurisprudence, through metaphor in the analysis of myth, and through semiotics as a way of comprehending a sentient landscape.